Heat stress in dairy cows: A review of abiotic and biotic factors, with reference to the subtropics - LM Erasmus; E van Marle-Köster (South African Journal of Animal Science)
Heat stress has been identified as one of the major challenges for livestock production. Global temperatures are steadily increasing, with South African temperatures increasing at nearly twice the global rate. Of the livestock used for food production, dairy cows are the most sensitive to thermal changes, which have detrimental effects on their health, welfare, and overall productivity. Several abiotic factors that influence the heat load experienced by the cow are not commonly included in thermal indices used to measure heat stress; these include solar radiation, wind speed, and soil quality. Furthermore, the thermal comfort zone of cows has been altered by years of intense selection for increased milk yield, causing cows to become heat stressed at lower temperatures. Considering the abiotic and biotic factors affecting the cow’s heat load, it can be argued that dairy cows in tropical and subtropical climates are experiencing constant heat stress. In this review, the abiotic and biotic factors influencing the heat load experienced by dairy cows are reviewed, along with the available thermal indices that can be utilised at farm level.